2004
DOI: 10.1182/blood-2004-03-0824
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis, intracellular sorting, and processing of exosomes by dendritic cells

Abstract: IntroductionDendritic cells (DCs) are antigen (Ag)-presenting cells (APCs) that function as biosensors of the cellular microenvironment by detecting the presence of signals that determine T-cell tolerance or immunity. 1,2 To accomplish this task, DCs acquire extracellular Ags by receptor-mediated endocytosis, macropinocytosis, or phagocytosis [3][4][5] ; by incorporation of microvesicles shed from the surface of neighboring cells, 6,7 and by their recently described interaction with nanovesicles (Յ 100 nm) ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
817
2
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 924 publications
(873 citation statements)
references
References 56 publications
31
817
2
9
Order By: Relevance
“…A diminution of exosome uptake by dendritic cells was observed in-vivo by inhibition of v3 integrins, CD11a and its ligands CD54, antibodies directed against the tetraspanins CD9 and CD81, or a soluble analogue of phosphatidylserine (PS) [71]. Thus exosomes adhesion to the recipient cell membrane are mediated through lipids (PS) and ligand-receptor interactions.…”
Section: Molecular Interaction Of Exosomes With Recipient Cell Peripherymentioning
confidence: 99%
“…A diminution of exosome uptake by dendritic cells was observed in-vivo by inhibition of v3 integrins, CD11a and its ligands CD54, antibodies directed against the tetraspanins CD9 and CD81, or a soluble analogue of phosphatidylserine (PS) [71]. Thus exosomes adhesion to the recipient cell membrane are mediated through lipids (PS) and ligand-receptor interactions.…”
Section: Molecular Interaction Of Exosomes With Recipient Cell Peripherymentioning
confidence: 99%
“…We next assessed whether membrane proteins that are known to be present in exosomes, such as LAMP-1, LAMP-2, ICAM-1, and transferrin receptor (TfR), also co-segregate with the 48-kDa TNFR1 exosome-like vesicles in the LDL fraction of human plasma [13][14][15][16]. As shown in Figure 4A, LAMP-1, LAMP-2, ICAM-1 and TfR co-segregated with the HDL fraction and were not detected in the LDL fraction.…”
Section: Typical Exosome Membrane Proteins Co-segregate With the Hdlmentioning
confidence: 99%
“…First, exosomes can either be internalized or captured at the cell surface where they remain [4]. Both of these outcomes have been observed in dendritic cells [50]. Segura et al [51] observed CD8 + dendritic cells capture exosomes via dendritic cell (DC) lymphocyte function-associated antigen 1 (LFA-1) at the surface for presentation of exosome-borne major histocompatibility complex (MHC)-peptide complexes to CD4 + T cells.…”
Section: Fate Of Exosomesmentioning
confidence: 99%
“…This process was dependent on intracellular adhesion molecule 1 (ICAM-1) expression on exosomes and is termed Bcross-dressing^ [55]. Another method by which DCs could capture exosomal antigens is through internalization, processing, and repackaging of endocytosed exosomal antigens into the endosomal pathway for representation on DC MHC II to naïve CD4 + T cells [50]. This process was documented in elegant experiments by Morelli et al [50].…”
Section: Fate Of Exosomesmentioning
confidence: 99%
See 1 more Smart Citation